RETRACTED: The Pragmatic Function of Speech for Elementary Students: Indonesian Teaching in Australia - Setiawan Edi Wibowo; Aurora Adina Cholomeischi; Tudor Colomeischi; Kordula Schulze (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
Following a rigorous examination and careful consideration of the article published in Jurnal Prima Edukasia entitled